Proses Perencanaan dan Penganggaran Anggaran Pendapatan dan Belanja Daerah: Studi Konsistensi Proses Perencanaan dan Penganggaran Pemerintah Kota Pangkalpinang Tahun Anggaran 2018-2022 - Failasophia Karima; Choirul Saleh; Sarwono Sarwono (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
The consistency between planning and budgeting is important because it is a marker for local governments in assessing the performance of all government programs and activities, whether they are running well and according to the goals set. The difference in consistency in the Pangkalpinang City Government occurs from year to year. Still, there is a commitment from the Regional Head to build consistency between planning and budgeting to realize community welfare. This research has a purpose: to find out and analyze how the consistency between planning and budgeting in the 2018 to 2020 fiscal year is through an analysis of the planning process and the budgeting process to see what factors support this consistency. The research method used uses a qualitative approach and analysis through the Interactive Model of Miles and Huberman. The results obtained from the research are planning and budgeting process in the Pangkalpinang City Government is still not consistent. The research locus is at the Regional Development Planning and Research Agency of the Pangkalpinang City, Regional Finance Agency of Pangkalpinang City, and Regional House of Representatives Budget Agency of Pangkalpinang City. Each year, the consistency that occurs is different in the Regional Government Work Plan (Rencana Kerja Pemerintah Daerah or RKPD). The highest consistency is found at the end of the Regional Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Daerah or RPJMD), which in this research falls on the 2018 Regional Government Work Plan (RKPD).